The effect of it practices on supply chain capabilities within Abu Dhabi monitoring and control center in UAE - Al Nuaimi, Saeed Khalfan Saeed Rashed (2023)
Businesses are increasingly relying on information technology to improve their supply chain capabilities. However, previous evidence demonstrates that investing in IT practices does not ensure improved supply chain capabilities. Using the assumptions of the resource-based view, the study aims to test the effect of information technology practices on supply chain capabilities. This study employs simple random sampling and obtained 361 respondents from the sample. The structural equation modelling approach is used to test theoretical predictions underlying the relationship among dimensions of IT practices and supply chain capabilities based on data obtained from Abu Dhabi monitoring and control centres. The results suggest that IT capability has a positive impact on supply chain capabilities. The study makes an empirical contribution to the theoretical by demonstrating the value of the multidimensional representation and analysis of IT practices and supply chain capabilities. For practical contribution, the application of IT practices provides great conveniences for cooperation among supply chain companies.